Pemberian Bantuan Untuk Warga dan Trauma Healing Bagi Anak-Anak Korban Bencana Gempa Bumi Cianjur - Asep Sofwan Munandar (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The community service activities carried out were the provision of basic food assistance, treatment to community members and trauma healing for children of Cianjur earthquake victims. This activity is a form of concern for the STIE Kalpataru academic community for the disaster that occurred, namely the earthquake in Cianjur in November 2022. This activity involved all elements of both leaders, lecturers, staff and students on the STIE Kalpataru campus, both as donors and those who took direct action to the disaster site. It is hoped that the action carried out by the STIE Kalpataru academic community can slightly ease the burden on the affected community, and can restore their spiritual mentality to be able to rise again.